Digital storytelling projects in developing Indonesian EFL pre-service teachers’ metasemiotic awareness and professional competence - Nur Arifah Drajati; Lynde Tan; Agustina Tyarakanita; Surya Agung Wijaya (Indonesian Journal of Applied Linguistics, 2023)
Despite the widely-cited potential of digital storytelling (DST), its use in EFL education remains under-explored in Indonesia. Thus, EFL pre-service teachers (PSTs) in Indonesia are not sufficiently prepared to create digital and multimodal teaching materials using pedagogical approaches like DST since  EFL education still prioritizes language and has not yet acknowledged other meaning-making modes for communication. In order to fill in the gap, we invited 20 pre-service teachers (aged 22 to 24) in Central  Java to be involved in our study. Employing a case study with intervention and using classroom observations, artifacts, and reflections to collect the data, this study aimed to increase pre-service teachers’ metasemiotic awareness and professional competence by involving these PSTs in examining the linguistic and visual modes whilst creating digital stories for EFL teaching. Furthermore, we discussed the approach to facilitate the processes to achieve this dual aim. The findings highlighted both the importance of teaching EFL from a multimodal approach and the pedagogical implications for Indonesian EFL pre-service teacher education.